(3GdbQH aj aVGFd GdYQHs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s
(3ChdgG (B:s
(3bO PcQJ bhd QShd Gddg Udi Gddg Ydjg hSde (B: (3dh QCjJge aieLGdSge dgHJge , bGd YOi Hf MGJe (B: (3abGd QShd Gddg Udi Gddg Ydjg Sde (B: (3jG eYTQ GdfGS CMHhG bQjTkG s
(3BNQgG (B:s
(3aVd Hfi fGLjI hge ef bQjT MOKfG TYHI Cf QShd Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B120s
(3YdjgG ebGHdIs
(3hgj HZjQ YfhGf hbO cJH YdjgG GdCSJGP eMeO YHO GdMi GdcJGfi CfgG GdbQH ai aVGFd GdYQH hgj ef ecJHJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B321 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs